2019
DOI: 10.5194/wes-2019-86
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How wind speed shear and directional veer affect the power production of a megawatt-scale operational wind turbine

Abstract: Abstract. Most megawatt-scale wind turbines align themselves into the wind as defined by the wind speed at or near the center of the rotor (hub height). However, both wind speed and wind direction can change with height across the area swept by the turbine blades. A turbine aligned to hub-height winds might experience suboptimal or superoptimal power production, depending on the changes in the vertical profile of wind, or shear. Using observed winds and power production over 6 months at a site in the high plai… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 52 publications
2
28
0
Order By: Relevance
“…In contrast, Eriksson et al [50] examined the effect of wind veer and the Coriolis force on an idealized farm-to-farm interaction case, in which the estimated power production was found to increase with the inclusion of the wind veer effect. Murphy et al [51] concluded that the influence of wind veer on turbine power production is strongly tied with wind speed, in which a large wind veer angle generally results in power gains at a wind speed exceeding 10 m/s. Below this threshold value, the impact of wind veer appears to be somewhat negligible.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Eriksson et al [50] examined the effect of wind veer and the Coriolis force on an idealized farm-to-farm interaction case, in which the estimated power production was found to increase with the inclusion of the wind veer effect. Murphy et al [51] concluded that the influence of wind veer on turbine power production is strongly tied with wind speed, in which a large wind veer angle generally results in power gains at a wind speed exceeding 10 m/s. Below this threshold value, the impact of wind veer appears to be somewhat negligible.…”
Section: Introductionmentioning
confidence: 99%
“…Not only wind speed but also wind direction is a relevant parameter of wind power output. Several studies have shown that the occurrence of large directional change results in lower turbine performance [45,46]. The measured and simulated wind direction at the WINSENT test-site are presented in Figure 9 Figure 9b.…”
Section: Comparison With the Uas Measurementsmentioning
confidence: 99%
“…The rotor-equivalent formulation area weights the effect of the variables to account for variations as a function of height within the wind turbine rotor-layer. Therefore, in case of wind speed, the rotor equivalent formulation takes into account effect of wind speed shear and wind direction veer each of which has shown to have, on an average, an effect of around 5% on wind power generation 22,23 . Once the rotor equivalent values are calculated, the wind power can be estimated using:…”
Section: Wind Power Datasetmentioning
confidence: 99%